2020
DOI: 10.1186/s12931-020-1312-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation and mortality in patients with comorbid COPD and heart failure: a systematic review and meta-analysis

Abstract: Background: Discrepancy exists amongst studies investigating the effect of comorbid heart failure (HF) on the morbidity and mortality of chronic obstructive pulmonary disease (COPD) patients. Methods: MEDLINE and Embase were searched using a pre-specified search strategy for studies comparing hospitalisation, rehospitalisation, and mortality of COPD patients with and without HF. Studies must have reported crude and/or adjusted rate ratios, risk ratios, odds ratios (OR), or hazard ratios (HR). Results: Twenty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 57 publications
(170 reference statements)
1
33
0
Order By: Relevance
“…Additionally, COPD can lead to PHTN, with subsequent right heart failure 15,16 . Patients with either COPD or HF have a greater proportion of all‐cause hospitalizations and mortality, with an increased risk when COPD is associate with HF 17,18 . In spite of this reported increased morbidity and mortality, individuals with COPD are less likely than non‐COPD patients to be prescribed evidence‐based pharmacological HF therapies 19‐21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, COPD can lead to PHTN, with subsequent right heart failure 15,16 . Patients with either COPD or HF have a greater proportion of all‐cause hospitalizations and mortality, with an increased risk when COPD is associate with HF 17,18 . In spite of this reported increased morbidity and mortality, individuals with COPD are less likely than non‐COPD patients to be prescribed evidence‐based pharmacological HF therapies 19‐21 .…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Patients with either COPD or HF have a greater proportion of all-cause hospitalizations and mortality, with an increased risk when COPD is associate with HF. 17,18 In spite of this reported increased morbidity and mortality, individuals with COPD are less likely than non-COPD patients to be prescribed evidence-based pharmacological HF therapies. [19][20][21] There is a There is a rapidly growing number of individuals with AHF with a mortality that could be as high as 80% at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…COPD is frequent and often undiagnosed (and hence untreated) among patients with chronic HF, at rates of 13 to 39% 56 . Moreover, COPD is associated with higher mortality in patients with chronic HF 58 . Similarly, the prevalence of COPD is high among patients with established IHD, but, as in chronic HF, is grossly underdiagnosed 56,59 .…”
Section: Copd As Comorbidity Of Other Frequent Chronic Diseasesmentioning
confidence: 99%
“…[3] Nevertheless, a meta-analysis of randomized controlled trials showed that the treatment with budesonide-an inhaled corticosteroid (ICS)-did not increase the risk of pneumonia. [5] Right heart failure is a common and serious complication in patients with COPD, which, when combined with right heart failure, can increase hospitalization rates [6,7] and all-cause mortality. [7][8][9][10] Recent studies showed that patients with both COPD and right heart failure may bene t from glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Right heart failure is a common and serious complication in patients with COPD, which, when combined with right heart failure, can increase hospitalization rates [6,7] and all-cause mortality. [7][8][9][10] Recent studies showed that patients with both COPD and right heart failure may bene t from glucocorticoids. In a real-world study with a 9year follow-up, the use of either ICS alone or long-acting beta-agonist (LABA)-ICS improved overall survival in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%